(untitled) (Annals of Medical Research, 2021)
Aim: Adequate vitamin D levels may reduce the risk of multiple sclerosis (MS) development and progress. It is believed that a number of genes cause the disease, including the genes that function on vitamin D metabolism, although information about the role of the said genes is quite contradictory. We aimed to investigate the status of serum vitamin D and ApaI, FokI, and BsmI gene polymorphisms of the vitamin D receptor in Turkish MS patients with different types and severities of the disease. Materials and Methods: The patients were divided into three groups in accordance with the types of MS: relapsing-remitting MS (RRMS), secondary progressive MS (SPMS), and primary progressive MS (PPMS). Serum D vitamin level was studied, and polymerase chain reaction (PCR) applications were performed by designing primers suitable for the vitamin D receptor (VDR) gene regions in which FokI (rs2228570), BsmI (rs1544410), and ApaI (rs7975232) polymorphisms are localized. The Expanded Disability Status Scale (EDSS) was utilized to determine the disability status of MS patients. Results: Although vitamin D levels were inadequate in MS patients and controls, the mean serum vitamin D level of MS patients was significantly higher than the controls (p<0.05). There was a statistically significant correlation with A/A, C/C, and A/C genotypes in SPMS patients and with ApaI A/A and A/C genotypes in PPMS patients. The rate of the EDSS score in the range of 0-6 was significantly higher in MS patients with BsmI G/G genotype in comparison with the other genotypes (p<0.05). Conclusion: In the Turkish population, while all alleles of the ApaI gene are associated with SPMS, the A/A and A/C alleles of ApaI are related to PPMS, and the BsmI G/G genotype may be associated with less disability in MS patients.